Two Models of the Auditor ‐ Client Interaction: Tests with United Kingdom Data* - HANSEN, STEPHEN C.; WATTS, JOHN S. (Contemporary Accounting Research, 1997)
Abstract. Accounting research contains two distinct approaches to the interaction between accounting management and the independent auditor. Game theory suggests that the auditor's testing strategy will affect the manager's reporting strategy and that the two strategies form an equilibrium. The game‐theoretic approach views the auditor as active, in that the auditor acknowledges the effect that his or her testing strategy has on the manager's reporting. In contrast, in the decision‐theoretic approach, the auditor tests reports, but ignores the effect that such testing might have on the manager's reporting behavior. Essentially, the decision‐theoretic approach views the auditor as passive, taking the reporting strategy as given when designing tests. We use United Kingdom data to estimate both models and test their validity using nested hypothesis tests. Our results demonstrate that the active, game‐theoretic model better describes the auditor‐manager interaction. This is the first empirical validation of the game‐theoretic model using archival accounting data.